Association mapping of quantitative trait loci for carcass and meat quality traits at the central part of chromosome 2 in Italian Large White pigs - Cepica, S; Zambonelli, P; Weisz, F; Bigi, M; Knoll, A; Vykoukalová, Z; Masopust, M; Gallo, M; Buttazzoni, L; Davoli, R (Meat science, 2013)
Association mapping of the central part of porcine chromosome 2 harboring QTLs for carcass and meat quality traits was performed with 17 gene-tagged SNPs located between 44.0 and 77.5 Mb on a physical map (Sscrofa10.2) in Italian Large White pigs. For the analyzed animals records of estimated breeding values for average daily gain, back fat thickness, lean cuts, ham weight, feed conversion ratio, pH1, pHu, CIE L*, CIE a*, CIE b* and drip loss were available. A significant QTL for fat deposition (adjusted P=0.0081) and pH1 (adjusted P=0.0972) to MYOD1 at position 44.4 Mb and a QTL for growth and meatiness (adjusted P=0.0238-0.0601) to UBL5 at position 68.9 Mb were mapped. These results from association mapping are much more accurate than those from linkage mapping and facilitate further search for position candidate genes and causative mutations needed for application of markers through marker assisted selection.
Keywords: prasata; Swine; fenotyp; Chromosome Mapping; Male; Breeding; Phenotype; maso; kvalita jídla; MyoD Protein; Hydrogen-Ion Concentration; mužské pohlaví; jednonukleotidový polymorfismus; chov; Body Weight; koncentrace vodíkových iontů; lokus kvantitativního znaku; Animals; Polymorphism, Single Nucleotide; ženské pohlaví; mapování chromozomů; Quantitative Trait Loci; zvířata; Food Quality; Meat; Female; tělesná hmotnost